Effect of capillary forces on the correlation between nanoscale adhesion and friction of polymer patterned surfaces. (October 2017) - Pendyala, Prashant; Kim, Hong Nam; Grewal, Harpreet S.; Cho, Il-Joo; Yoon, Eui-Sung
Abstract: A general relation between adhesion and friction was elusive. This was partly due to the limitations in experimentally configuring the wide variety of geometrical and chemical cues encountered at a sliding contact. We study the combined influence of capillary and van der Waals forces on the correlation between the adhesion (pull-off force) and friction of polymer patterns. We report the existence of master curves in plot of adhesion versus friction, spanning nearly two orders of magnitude, characteristic of the effective lateral contact stiffness of the contact determined by geometry and capillary forces. Further, we showed how nanocylindrical patterns, micropatterns and PTFE-coated PMMA flat surfaces subjected to varying capillary forces displayed similar sliding characteristics despite their large differences in contact characteristics. Graphical abstract: Highlights: Geometrically intricate nanopatterns were generated using capillary force lithography and nano-drawing techniques. Effect of capillary forces on correlation between adhesion and friction was investigated. A master curve in adhesion vs. friction graph spanned for two orders of magnitude of adhesion force. The slope of the curves was dependent on the lateral contact stiffness due to geometry and adhesion. Results widen the fundamental understanding of nano-topographical interactions and improve the ability to predict nanofriction.